Il supporto psicologico telefonico a partire dall’analisi dei bisogni: la creazione dello strumento Analisi dei Bisogni Assistenza Covid-19/ABACO-19 - Ersilia Cossu; Gianluigi Carta (Rivista di Psicologia dell'Emergenza e dell'Assistenza Umanitaria, 2020)
n this article, the authors aim at describing the field experience related to the telephone psychological support activity in Sardinia during the Covid-19 emer-gency. Specifically, they will illustrate the protocols and procedures used by psy-chologists according to the psychosocial model of Psicologi per i Popol (PxP).They also aim to describe the work of needs analysis, a fundamental element for intervention planning, which is an essential tool of the emergency and humanitar-ian assistance psychologist in order to promote effective listening and be able to enhance the resources of the people who call on the direct line, as well as fami-lies, according to an integrated psychosocial approach that characterizes the in-tervention of PxP.In line with the psychosocial approach as a theoretical assumption applied in op-erational interventions in emergencies, they describe the different organisational and operational phases of the service offered to the population, the role of the psychologist and the team of operators involved, the intervention methodology and the analysis of the data collected.